Non-Invasive Targeted Peripheral Nerve Ablation Using 3D MR Neurography and MRI-Guided High-Intensity Focused Ultrasound (MR-HIFU): Pilot Study in a Swine Model. - Merel Huisman; Robert M Staruch; Michelle Ladouceur-Wodzak; Maurice A van den Bosch; Dennis K Burns; Avneesh Chhabra; Rajiv Chopra (PLoS ONE)
Purpose Ultrasound (US)-guided high intensity focused ultrasound (HIFU) has been proposed for noninvasive treatment of neuropathic pain and has been investigated in in-vivo studies. However, ultrasound has important limitations regarding treatment guidance and temperature monitoring. Magnetic resonance (MR)-imaging guidance may overcome these limitations and MR-guided HIFU (MR-HIFU) has been used successfully for other clinical indications. The primary purpose of this study was to evaluate the feasibility of utilizing 3D MR neurography to identify and guide ablation of peripheral nerves using a clinical MR-HIFU system. Methods Volumetric MR-HIFU was used to induce lesions in the peripheral nerves of the lower limbs in three pigs. Diffusion-prep MR neurography and T1-weighted images were utilized to identify the target, plan treatment and immediate post-treatment evaluation. For each treatment, one 8 or 12 mm diameter treatment cell was used (sonication duration 20 s and 36 s, power 160-300 W). Peripheral nerves were extracted < 3 hours after treatment. Ablation dimensions were calculated from thermal maps, post-contrast MRI and macroscopy. Histological analysis included standard H&E staining, Masson's trichrome and toluidine blue staining. Results All targeted peripheral nerves were identifiable on MR neurography and T1-weighted images and could be accurately ablated with a single exposure of focused ultrasound, with peak temperatures of 60.3 to 85.7°C. The lesion dimensions as measured on MR neurography were similar to the lesion dimensions as measured on CE-T1, thermal dose maps, and macroscopy. Histology indicated major hyperacute peripheral nerve damage, mostly confined to the location targeted for ablation. Conclusion Our preliminary results indicate that targeted peripheral nerve ablation is feasible with MR-HIFU. Diffusion-prep 3D MR neurography has potential for guiding therapy procedures where either nerve targeting or avoidance is desired, and may also have potential for post-treatment verification of thermal lesions without contrast injection.